2003
DOI: 10.1007/s10267-003-0101-8
|View full text |Cite
|
Sign up to set email alerts
|

Conspecificity of Endothia eugeniae and Cryphonectria cubensis: a re-evaluation based on morphology and DNA sequence data

Abstract: Cryphonectria cubensis and Endothia eugeniae are fungal pathogens of Eucalyptus and clove that were reduced to synonymy on the basis of results of crossinoculation studies, isozyme analysis, cultural studies, and morphology. A previous phylogenetic study on Cryphonectria, based on sequence variation in the ITS region of the ribosomal RNA operon, also supported the conspecificity of C. cubensis and E. eugeniae, but was based on only one E. eugeniae isolate. New collections from clove in Brazil and Indonesia hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 22 publications
5
33
0
Order By: Relevance
“…Countries where the identity has been confirmed based on DNA sequence comparisons: U.S.A. (Hawaii), Tanzania (Zanzibar), Kenya, Malawi, Mozambique, Indonesia, Singapore, Thailand, China (Hong Kong-ITS only), Australia (Myburg et al 1999a;Myburg et al 2003;Roux et al 2003;Gryzenhout et al 2004;Gryzenhout et al 2006b;Nakabonge et al 2006). Isolates from Vietnam, although previously reported as C. cubensis (Old et al 2003), are also shown for the first time to represent C. deuterocubensis based on DNA sequence data.…”
Section: Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Countries where the identity has been confirmed based on DNA sequence comparisons: U.S.A. (Hawaii), Tanzania (Zanzibar), Kenya, Malawi, Mozambique, Indonesia, Singapore, Thailand, China (Hong Kong-ITS only), Australia (Myburg et al 1999a;Myburg et al 2003;Roux et al 2003;Gryzenhout et al 2004;Gryzenhout et al 2006b;Nakabonge et al 2006). Isolates from Vietnam, although previously reported as C. cubensis (Old et al 2003), are also shown for the first time to represent C. deuterocubensis based on DNA sequence data.…”
Section: Distributionmentioning
confidence: 99%
“…Previous phylogenetic studies based on the rRNA internal transcribed spacer (ITS) regions, β-tubulin and histone H3 genes have consistently separated C. cubensis into two well-supported clades (Myburg et al 1999b;Myburg et al 2002;Myburg et al 2003;Gryzenhout et al 2004;Myburg et al 2004;Gryzenhout et al 2006a;Gryzenhout et al 2006c). One of these, referred to as the South American clade, accommodates isolates from countries in South and Central America, as well as likely introductions into western African countries such as Cameroon, Congo and the Democratic Republic of the Congo (Myburg et al 2002;Myburg et al 2003;Roux et al 2003;Gryzenhout et al 2006b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…: Britton (Melastomataceae, Mytales) (Nakabonge et al 2006a, Vermeulen et al 2011. Celoporthe indonesiensis infects S. aromaticum (L.) Merr & Perry in Indonesia (Myburg et al 2003, Chen et al 2011, while the Chinese species C. eucalypti and C. guangdongensis were collected from non-native Eucalyptus species and C. syzygii is known from non-native S. cumini (L.) Skeels (Chen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This rust disease is native on Myrtaceae in South and Central America and has adapted to infect Eucalyptus in that region (Coutinho et al 1998, Glen et al 2007). In addition, there are many recent examples of members of the Cryphonectriaceae, that are native on members of the Myrtales, adapted to infect Eucalyptus in Africa (Heath et al 2006) as well as South and Central America and Asia Hodges et al 1986;Myburg et al 2003;Rodas et al 2005). …”
Section: A Diverse Group Of Mycosphaerellaceae and Teratosphaeriaceaementioning
confidence: 99%